2020
DOI: 10.1111/sms.13647
|View full text |Cite
|
Sign up to set email alerts
|

Indexes of aortic wave reflection are not augmented in estrogen‐deficient physically active premenopausal women

Abstract: Background: Hypoestrogenemia due to menopause is associated with increased cardiovascular disease risk, in part due to elevated indexes of aortic wave reflection (AWRI) and central (aortic) blood pressure. We sought to investigate whether AWRI and central blood pressure are also augmented in hypoestrogenic exercise-trained premenopausal women with functional hypothalamic amenorrhea (ExFHA). Methods: In age-(pooled mean ± SEM, 24 ± 1 years), BMI-(21 ± 1 kg/m 2 ), and cardiorespiratory fitness-matched (45 ± 2 ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…290,291 In contrast, a growing number of studies have reported that carotid-femoral PWV, 288,291e294 AI x , 293,295 carotid artery stiffness, 294 or carotid and femoral artery compliance 296 are unchanged throughout the menstrual cycle. A similar lack of responsiveness in elastic large-artery stiffness has been reported across different phases of oral contraceptive use, 293,294 while active hypoestrogenic premenopausal women with functional hypothalamic amenorrhea have lower resting systolic arterial pressure, pulse pressure, and AI x @75 compared to fitness-matched eumenorrheic controls 297 in spite of their exaggerated MSNA responses to graded lower body negative pressure. 298 Numerous randomized controlled trials have sought to determine prospectively the effects of estrogen or combined hormone replacement therapy on arterial stiffness in postmenopausal women.…”
Section: Testosteronesupporting
confidence: 61%
“…290,291 In contrast, a growing number of studies have reported that carotid-femoral PWV, 288,291e294 AI x , 293,295 carotid artery stiffness, 294 or carotid and femoral artery compliance 296 are unchanged throughout the menstrual cycle. A similar lack of responsiveness in elastic large-artery stiffness has been reported across different phases of oral contraceptive use, 293,294 while active hypoestrogenic premenopausal women with functional hypothalamic amenorrhea have lower resting systolic arterial pressure, pulse pressure, and AI x @75 compared to fitness-matched eumenorrheic controls 297 in spite of their exaggerated MSNA responses to graded lower body negative pressure. 298 Numerous randomized controlled trials have sought to determine prospectively the effects of estrogen or combined hormone replacement therapy on arterial stiffness in postmenopausal women.…”
Section: Testosteronesupporting
confidence: 61%
“…A study by Hoch et al 17 found evidence of endothelial dysfunction in premenopausal (18- to 35-year-old) runners experiencing athletic amenorrhea. Additionally, a study by O’Donnell et al 18 found higher total peripheral resistance in premenopausal (18- to 35-year-old) exercising women experiencing functional hypothalamic amenorrhea compared with age and exercise-matched eumenorrheic women. Further, they reported that in the amenorrheic women, an acute bout of exercise did not alter their heart rate–corrected augmentation index (Aix75; a composite marker of arterial stiffness), suggesting a blunted vascular response to nitric oxide increases that occur during exercise.…”
Section: Introductionmentioning
confidence: 98%